Circular RNA circLMO1 Suppresses Cervical Cancer Growth and Metastasis by Triggering miR-4291/ACSL4-Mediated Ferroptosis - Ou, Rongying; Lu, Shun; Wang, Luhui; Wang, Yebo; Lv, Mingfen; Li, Tian; Xu, Yunsheng; Lu, Jieqiang; Ge, Ren-shan (Frontiers in Oncology, 2022)
Background: A number of studies have demonstrated that circular RNA (circRNA) plays a critical role in tumorigenesis and tumor progression. However, the biological effects of most circRNAs on cervical cancer remain unclear. Hsa_circ_0021087 (thereafter named circLMO1) is a circRNA generated from the circularization of exon 2 and exon 3 of LIM Domain Only 1 (LMO1) and first identified as a tumor suppressor in gastric cancer. We aimed to identify the role of circLMO1 in cervical cancer progression. Methods: CircLMO1 was verified through qPCR and Sanger sequencing. The biological role of circLMO1 in regulating cervical cancer growth and metastasis was investigated both in vitro and in the nude mouse xenograft tumor model. The dual luciferase reporter assay and rescue experiment were conducted to evaluate the interactions among circLMO1, microRNA (miR)-4291, and acyl-CoA synthetase long chain family member 4 (ACSL4). The role of circLMO1 in regulating ferroptosis was assessed by analyzing lipid reactive oxygen species (ROS), and malonyl dialdehyde (MDA), and glutathione (GSH) content. Results: The level of circLMO1 was down-regulated in cervical cancer tissues and was associated with the International Federation of Gynecology and Obstetrics (FIGO) staging. Functionally, circLMO1 overexpression inhibited cervical cancer growth and metastasis both in vitro and in vivo, whereas circLMO1 depletion promoted cervical cancer cell proliferation and invasion. Mechanistically, circLMO1 acted as a competing endogenous RNA (ceRNA) by sponging miR-4192 to repress target gene ACSL4. CircLMO1 promoted cervical cancer cell ferroptosis through up-regulating ACSL4 expression. Overexpression of miR-4291 or knockdown of ACSL4 reversed the effect of circLMO1 on facilitating ferroptosis and repressing cervical cancer cell proliferation and invasion. Conclusion: CircLMO1 acted as a tumor suppressor of cervical cancer by regulating miR-4291/ACSL4-mediated ferroptosis, and could be a promising biomarker for the clinical management of cervical cancer.